Li‐Ion Batteries: Understanding the Outstanding High‐Voltage Performance of NCM523||Graphite Lithium Ion Cells after Elimination of Ethylene Carbonate Solvent from Conventional Electrolyte (Adv. Energy Mater. 14/2021). Issue 14 (15th April 2021) - Klein, Sven; van Wickeren, Stefan; Röser, Stephan; Bärmann, Peer; Borzutzki, Kristina; Heidrich, Bastian; Börner, Markus; Winter, Martin; Placke, Tobias; Kasnatscheew, Johannes
Abstract : In article number 2003738, Martin Winter, Tobias Placke, Johannes Kasnatscheew and co‐workers report that a simple elimination of ethylene carbonate (EC) from conventional electrolytes counterintuitively boosts the high voltage performance in Li‐ion batteries. It is attributed to the beneficially formed Li x PO y F z ‐species, which can scavenge the hazardous transition metals (Ni, Co, Mn) dissolved from NCM cathodes.